Nilai-nilai Kearifan Lokal Kesehatan dalam Tradisi Kolak Ayam (Sanggring) Desa Gumeno Kecamatan Manyar Kabupaten Gresik - Zanuba, Meidita; Nely Zulfatin Ni’amah; Alfisyah Nurhayati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
The "Kolak Ayam" tradition in Gumeno Village is a typical cultural celebration carried out by the village community during the month of Ramadan. This tradition has historical origins close to the reign of King Sunan Dalem of the Giri Kedaton Kingdom and important events that occurred at that time. This tradition begins with the story of Sunan Dalem who fell seriously ill while building a mosque in his village. Through instructions in his dream, Sunan Dalem and the village community created a special food called "Kolak Ayam". Sunan Dalem recovered from his illness after eating this dish, and the tradition became a symbol of healing and celebration for the Gumeno people. This research aims to find out how people believe "Kolak Ayam" can cure diseases. This data collection technique uses interview techniques, observation and literature study. The results of research show that until now "Kolak Ayam" (Sanggring) is believed to be able to cure diseases. People believe that "Kolak Ayam" can cure diseases, this is caused by two things, the first is from the ingredients used to make "Kolak Ayam" which has many benefits, the second comes from Sunan Dalem's blessing and this belief is because in the past Sunan Dalem was cured by eating "Kolak Ayam ", people believed that "chicken compote" could cure the disease.